Examining Master’s Students’ Success at a Hispanic-Serving Institution - Kenneth John Tobin; Jacinto De La Cruz Hernandez; José R. Palma; Marvin Bennett; Nandita Chaudhuri (Trends in Higher Education)
This work examines the indicators of master’s students’ persistence from 2014 to 2021 at a Hispanic-Serving Institution (HSI) in the southern United States. Demographic and academic variables were used in a logistic regression model to predict students’ successful completion across sixteen master’s programs. In this two-fold study, first, we examined the impact of COVID-19 on students enrolled in twelve face-to-face (F2F) programs and evaluated their performance against a pre-pandemic baseline period. Second, we compared student performance in four accelerated online programs against a pre-accelerated baseline. Most demographic variables were insignificant, while all academic variables were significant across program types. However, GPA became an insignificant variable when the F2F programs were forced to move online during the COVID-19 pandemic. During this period, GPA also increased for students who had discontinued their studies. The accelerated online programs recorded a significant decrease in terms enrolled (Term Count) compared to the pre-accelerated baseline. These results add to the limited literature on student success at the master’s level in HSIs, thus filling a vital knowledge gap. This study provides two case studies focusing on how the pandemic and the accelerated online learning model impacted academic persistence at the master’s level at an HSI.